2012
DOI: 10.1159/000342076
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Fatal Fulminant Myocarditis Presenting as an Acute ST-Segment Elevation Myocardial Infarction and Persistent Ventricular Tachyarrhythmia Associated with Influenza A (H1N1) Virus in a Previously Healthy Pregnant Woman

Abstract: Several studies have reported influenza A (H1N1) virus as a cause of fulminant myocarditis. We report the first fatal case of fulminant myocarditis presenting as an acute ST-segment elevation myocardial infarction and ventricular tachyarrhythmia associated with influenza A (H1N1) in a previously healthy pregnant woman. A 38-year-old Asian woman, gravida 3, para 1-0-1-1, presented with flu-like symptoms. Initially, she developed wide-complex tachycardia requiring several defibrillations and was later intubated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Another study has shown abnormal ECG findings on days 1, 4, 11, and 28 days after the influenza disease presentation in young adults (35). Some groups also have shown an association between influenza infection and ventricular arrhythmias and hospitalizations of heart failure (32,33,36,37).…”
Section: Association Between Influenza Virus Infection and Cardiovascmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study has shown abnormal ECG findings on days 1, 4, 11, and 28 days after the influenza disease presentation in young adults (35). Some groups also have shown an association between influenza infection and ventricular arrhythmias and hospitalizations of heart failure (32,33,36,37).…”
Section: Association Between Influenza Virus Infection and Cardiovascmentioning
confidence: 97%
“…Several clinical reports have shown that influenza vaccination reduces influenza-associated cardiovascular events (4,36,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Gwini et al identified that the influenza vaccine-induced protective effect is greater in those receiving the vaccine before mid-November (49).…”
Section: Association Between Influenza Virus Infection and Cardiovascmentioning
confidence: 99%
“…Extra-respiratory tract complications are occasionally described in pregnant women. These include the development of myocarditis after infection with A(H1N1)pdm09 [28,29], and the development of an encephalopathy associated with a seasonal H3N2 IAV infection from which viral RNAwas detected in cerebrospinal fluids [30].…”
Section: Influenza a Virus Pathogenesis In Pregnant Womenmentioning
confidence: 99%
“…We also observed AF, RBBB, LBBB and type I AV block. In literature we found some case reports on rhythm disorders in swine flu like VF, AF, complete heart block, first degree heart block, bradycardia and wide complex tachycardia [13,14,16,20]. Although precise mechanisms by which ECG manifestations are produced in H1N1 influenza are still unknown it may be a direct cytolytic effect of virus on myocardial cells with cytotoxic immunologic interaction, ischemia due to intracapillary thrombosis, inflammatory edema pressing AV node and other conduction tissue or primarily affecting conduction tissue/AV nodal pacemaker cells resulting in resting membrane potential changes [13,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In our study 4 patients developed STEMI, 2 of them were known case of pre-existing CAD and 2 were not (one 60 year old male and the other 64 year female), the values of Troponin I, NT-proBNP and CPK-MB in these 2 new cases was highly raised (778.2/7164/8.94 and 190.9/7016/6.3 respectively). It has been shown that influenza may precipitate MI [20,22,23]. It has also been observed that incidence…”
Section: Discussionmentioning
confidence: 99%